Faktor-faktor Yang Mempengaruhi Kemampuan Manajer Dalam Melaksanakan Tugas Dan Hubungannya Dengan Keberhasilan Usaha Koperasi Unit Desa Di Kabupaten Kapuas Provinsi Kalimantan Tengah - Tonich Uda (FKIP, Universitas Palangka Raya, 2015)
The objectives of this study were to analyse the effect of education, training, experience and compensation upon the managers ability in conducting job and the relationships with the success of KUD in the district of Kapuas at Central Kalimantan Province. The hypothesis of this study were: (1) Factors and elements of managers ability [Education (X1), Training (X2), Experience (X3) and Compensation (X4)] affect positively to managers ability in conducting their job at KUD; (2) Managers ability in conducting their job (Y) affect positively on the success of KUD. A survey was applied in the district of Kapuas, Central Kalimantan. In this study 45 KUD were sorted out as a sample and 45 managers of these KUD in the district. The hypothesis were tested using Structural Equation Modeling Analysis (SEM) and using LISREL 8.0 program. The results of this study indicated that (1) education, training, experience and compensation factors positively affected to the managers'ability in conducting their job. (2) The ability of managers in conducting their job in turn positively would affect to the success of KUD.